The blue sweater bridging the gap between rich and poor in an interconnected world - Novogratz, Jacqueline (Michigan Brilliance Audio, 2009)
The Blue Sweater is the inspiring story of a woman who left a career in international banking to spend her life on a quest to understand global poverty and find powerful new ways of tackling it. It all started back home in Virginia, with the blue sweater, a gift that quickly became her prized possession?until the day she outgrew it and gave it away to Goodwill. Eleven years later in Africa, she spotted a young boy wearing that very sweater, with her name still on the tag inside. That the sweater had made its trek all the way to Rwanda was ample evidence, she thought, of how we are all connected, how our actions?and inaction?touch people every day across the globe, people we may never know or meet.
Keywords: Poverty